PSXII-6 In vitro fermentative parameters of diets containing increasing inclusions of WDG for feedlot sheep - Bertoco, João Pedro A (J Anim Sci, 2019)
The objective of this work was to evaluate the effects of increasing inclusion of WDG in diets for sheep on in vitro gas production, pH, N-NH3 and VFA. Three ruminally-cannulated adult male sheep were used as donors of inoculum. Treatments consisted of diets containing 0, 15, 30 and 45% WDG inclusion on dry matter basis with forage: concentrate ratio of 20:80. The experimental design was completely randomized with repeated measurements over time (3, 6, 12 and 24 hours). Flasks with a volume of 50 mL were used for incubation. Approximately 0.2 g of sample, 10 mL of inoculum and 20 mL of McDougall buffer solution were added into the flasks. Each time consisted of 7 flasks per treatment and 2 flasks without sample (n = 120). Gas production was measured using a pressure transducer. Concentration of N-NH3 was determined using micro-Kjeldhal apparatus and VFA was determined by gas chromatography. The data were analyzed using MIXED procedure of SAS. Orthogonal contrasts were used to determine the linear and quadratic effect of WDG inclusion. Increasing linear effect was observed for pH (P < 0.05) when WDG was included, with a lower value for 0% WDG (6.90). For N-NH3 and gas production, a linear decreasing effect (P < 0.05) was observed, ranging from 12.60 to 8.45 mg/dL and 93.47 to 58.40 mL/g incubated for 0 and 45% WDG, respectively. The total concentration of VFA did not present a significant effect. Butiric acid showed a linear effect (P < 0.05) ranging from 9.50 to 8.69 mM/L for 0 and 45% WDG, respectively. The acetic acid had a quadratic effect (P < 0.05), ranging from 52.92 to 58.59 mM/L for 15 and 45% WDG, respectively. The results indicate that the inclusion of up to 45% WDG in feedlot sheep diets promoted lower in vitro fermentation without altering the total VFA concentration.